2021
DOI: 10.1111/dth.14947
|View full text |Cite
|
Sign up to set email alerts
|

Use of dermoscopy after punch removal of a veiled sea urchin spine

Abstract: With the increasing number of marine sports activities performed for leisure, cutaneous injuries caused by sea urchin spines have become common. Such injuries may cause immediate reactions such as local pain, erythema, and edema or delayed reactions such as arthritis and granuloma formation. To reduce the risk of complications, immediate extraction of the sea urchin spines after the initial injury is important. 1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Suarez-Conde et al 153 reported spines to appear as foreign bodies having a violaceous-black colour and a striated external surface placed either obliquely or transversely in the skin. Park et al 154 also demonstrated the retained spines in the tissue.…”
Section: Sea Urchin Spinesmentioning
confidence: 91%
“…Suarez-Conde et al 153 reported spines to appear as foreign bodies having a violaceous-black colour and a striated external surface placed either obliquely or transversely in the skin. Park et al 154 also demonstrated the retained spines in the tissue.…”
Section: Sea Urchin Spinesmentioning
confidence: 91%